Innate-like T cells straddle innate and adaptive immunity by revising antigen-receptor responsiveness - Wencker, Melanie (Nat Immunol, 2013)
The sub-classification of immunology into innate and adaptive immunity is challenged by innate-like T lymphocytes that use innate receptors to respond rapidly to stress despite expressing T cell antigen receptors, a hallmark of adaptive immunity. Explaining how such cells straddle innate and adaptive immunity, the current study shows that antigen receptor signaling, whose conventional role is to facilitate clonal T cell activation, is critical for innate-like T cell development but then is rapidly attenuated, thus accommodating the cells’ innate responsiveness. These findings permitted the identification de novo of an innate-like T cell subset, and argue that T cell hypo-responsiveness, a state traditionally implicated in tolerance, may be fundamental to T cells entering the innate compartment and thereby providing lymphoid stress surveillance.